Islamic education and the challenge of democratic citizenship: a critical perspective. Issue 6 (2nd November 2017) - Saada, Najwan; Gross, Zehavit
ABSTRACT: This article analyzes how concepts of liberal and progressive Islam, which have been developed in the political and theological academic literature, may inform the curriculum of Islamic education and the practice of religious educators in Islamic schools in the US. We investigate the meaning of in-faith Islamic education and how it can conform to the life in a democratic, multicultural, and multi-faith society. Liberal Islam challenges the transmission-oriented and rigid interpretations of Islam and seeks to appreciate and to contextualize the religious claims which are compatible with ideals of reflective education, rational thinking, mutual respect, and equal citizenship. It suggests that students become critical 'consumers' of Islam, its moral and civic purposes, and the cultural politics of religious interrogations.